Searching in a global environment: Finding information from and on foreign countries, regions and markets. (December 2014) - Weiss, Arthur
Global information is required to facilitate trade, international business expansion, research and for international comparisons. The amount of data available varies in what exists, its age and its accuracy. Information from one area may not be comparable with that from another. The global searcher needs to consider these points and why information may be findable, prior to searching. Anticipating such issues can aid the search approach – whether via a local search engine or by going directly to a range of websites holding relevant data. Global and national information can come from supranational bodies, governments, public and private sector organizations as well as specialist sites. Some information sources will require payment or a subscription to gain access.